2014
DOI: 10.1002/ejhf.52
|View full text |Cite
|
Sign up to set email alerts
|

Effect of increasing pump speed during exercise on peak oxygen uptake in heart failure patients supported with a continuous‐flow left ventricular assist device. A double‐blind randomized study

Abstract: Aims Continuous‐flow left ventricular assist device (CF‐LVAD) implantation is associated with improved quality of life, but the effect on exercise capacity is less well documented. It is uncertain whether a fixed CF‐LVAD pump speed, which allows for sufficient circulatory support at rest, remains adequate during exercise. The aim of this study was to evaluate the effects of fixed versus incremental pump speed on peak oxygen uptake (peak VO2) during a maximal exercise test. Methods and results In CF‐LVAD (Heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
92
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(98 citation statements)
references
References 27 publications
5
92
1
Order By: Relevance
“…This loop extends the time-history of shear stress exposure of the blood, increasing hemolysis and thromboembolism risks; (ii) the development of AV dysfunction, including acquired AS and AI, may reduce the likelihood of "bridge to myocardial recovery" in those patients for whom CF-LVAD support is projected to be temporary; and (iii) exercise-induced augmentation of cardiac output, correlated with fewer adverse events and a higher quality of life, may be limited by an incompetent valve. 13,18,19 Although not clinically proven, there is concern that even mild to moderate, continuous AI may lead to increased morbidity and mortality in patients on prolonged LVAD support. Theoretically, continuous AI could lead to elevated wedge pressures with resultant exercise intolerance and gradual end-organ dysfunction.…”
Section: The Peri-operative Periodmentioning
confidence: 99%
See 1 more Smart Citation
“…This loop extends the time-history of shear stress exposure of the blood, increasing hemolysis and thromboembolism risks; (ii) the development of AV dysfunction, including acquired AS and AI, may reduce the likelihood of "bridge to myocardial recovery" in those patients for whom CF-LVAD support is projected to be temporary; and (iii) exercise-induced augmentation of cardiac output, correlated with fewer adverse events and a higher quality of life, may be limited by an incompetent valve. 13,18,19 Although not clinically proven, there is concern that even mild to moderate, continuous AI may lead to increased morbidity and mortality in patients on prolonged LVAD support. Theoretically, continuous AI could lead to elevated wedge pressures with resultant exercise intolerance and gradual end-organ dysfunction.…”
Section: The Peri-operative Periodmentioning
confidence: 99%
“…Pulsatility with AV opening may benefit patient exercise tolerance and enhance LV myocardial recovery attempts. 13,18,19 A patent AV also provides a "bail-out" mechanism should acute CF-LVAD malfunction occur. As such, a bioprosthetic AVR may be considered for management of native AS in selected CF-LVAD recipients.…”
Section: Native Av Diseasementioning
confidence: 99%
“…Thus pressure-volume relations during exercise with increased pump speed are of general interest, and the chosen increase of +800 RPM in this study has previously been shown clinically safe. 5,6 Central pressures, CO, and mixed venous blood oxygen saturation (SvO 2 ) were measured by right heart catheterization (RHC), via the right internal jugular vein, using a Swan-Ganz catheter (Edwards Lifesciences, Irvine, California). Cardiac output was measured three times at each ramp step by standard thermodilution with cold water injection, and the average result was recorded.…”
Section: Measurements and Interventionsmentioning
confidence: 99%
“…(34,35) Brassard et al showed cardiac output increased at submaximal exercise with increased pump speed (at rest cardiac output was 6 ± 2.1 L/min; submaximal exercise 60W cardiac output was 8.7 ± 1.1 L/min). (34) But, this study did not demonstrate significant differences at maximal exercise between the increased pump speed and constant pump speed groups.…”
Section: Interventions To Improve Functional Statusmentioning
confidence: 99%